The impact of trade liberalisation on exports, imports, the balance of payments and growth: The case of Mexico - Penélope Pacheco-López (University of Kent, Department of Economics, 2004)
The aim of this paper is to disentangle the effects of trade liberalisation during the mid-1980s from the liberalisation involved in the North American Free Trade Agreement (NAFTA) on exports, imports and the balance of payments in Mexico. The main empirical results suggest that the trade reforms during the mid-1980s had a significant impact of trade, exports and imports; however, the effects of NAFTA are negligible. Since the mid-1980s, the propensity to import has exceeded the propensity to export and this has worsened the growth rate consistent with balanced trade, and this is a major explanation of the slowdown of Mexico's growth in recent years. NAFTA has not delivered the improved growth performance that was promised by Mexico's political leaders at the time.
Keywords: C22; F13; F32; F43; 330; Trade liberalisation; NAFTA; Exports; Imports; Balance of Payments; Mexico; Außenhandelsliberalisierung; Wirkungsanalyse; Außenwirtschaft; Zahlungsbilanz; Wirtschaftswachstum; Mexiko